Studying the volatility effect of agricultural exports on agriculture share of GDP: The case of Egypt - Osama Ahmed; Walid Sallam (African Journal of Agricultural Research, 2018)
This article aims to examine the long and short run relationship between agricultural exports and agriculture share of GDP. Links between series considered are assessed by co-integration analysis using Johansen co-integration technique and ECM-GARCH. Results indicate a positive link in the short and long term between agricultural exports and agriculture share of GDP, as well as co-integration between the pairs of series used. Also it can be found that increases in agricultural exports were followed by increases in agriculture share of GDP. Agriculture exports and agriculture share of GDP elasticities are 0.62. The past shocks and agricultural exports increased agriculture share of GDP volatility.
Keywords: F13; F14; F15; F40; Q17; 330; Agricultural exports; Agricultural economic growth; Co-integration analysis; Johansen co-integration; ECM-GARCH